DESIGN OF A PRODUCTION PLANT CARMINE AND ANNATO - Erazo E., Raymundo (2001)
In this work we present the design of a plant to produce Carmine and Annatto from Cochineal and annatto tree, respectively. The piant will be installed in Lima and all the equípments of the process will be build from stainless steel 316 with sanitary finishing. We estimate an inversion of US$ 351 650 to produce 12,7 Kg of Carmine and 15,5 Kg of Annatto per day. The quality of the products are among the required standards by the international market. The rentability of the process is 20,45% for Carmine and 36,90% for Annatto and a payment time of 2,11 years.